FACTORS AFFECTING THE PRODUCTION OF RICE FARMING IN POLENGA VILLAGE, KECAMATAN WATUBANGGA DISTRICT KOLAKA REGENCY - Muhammad Obi Kasmin; Kartomo Kartomo (Agribusiness Journal, 2020)
The productivity of rice farming is largely determined by the use of production factors such as land, seeds, fertilizers, pesticides and labor. High productivity will only be achieved when the allocation of production factors is done effectively and efficiently. This study aims to determine the effect of production factors on the production quantity of rice farming in the Polenga village, Watubangga district, Kolaka regency. The sample determination in this study was performed using the Slovin method, while the data analysis method used in this study was multiple linear regression analysis. The results showed that the production factor of land area had a significant effect on the quantity of rice farming production. Meanwhile, the production factors of the quantity of seeds, the amount of urea fertilizer, the amount of NPK fertilizer, the amount of pesticides and the quantity of workers did not have a significant effect on rice farming production in Polenga village.